2012
DOI: 10.1007/s11548-012-0800-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated measurement of mandibular cortical width on dental panoramic radiographs

Abstract: An automated MCW measurement technique is feasible using DPRs, and this method has a potential to identify asymptomatic osteoporotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…The levels of sensitivity and specificity associated with this index were heterogeneous and had a reciprocal relationship that varied in relation to the threshold chosen. A few studies reported a sensitivity >95% (Devlin et al 2007;Ezoddini Ardakani et al 2013;Kavitha et al 2013;Muramatsu et al 2013), while in other studies, this parameter did not reach 20% (Horner et al 2002;Marandi et al 2010;Mansour et al 2013). The same variability applied to the specificity levels (Appendix Table 4).…”
Section: Mandibular Cortical Widthmentioning
confidence: 89%
“…The levels of sensitivity and specificity associated with this index were heterogeneous and had a reciprocal relationship that varied in relation to the threshold chosen. A few studies reported a sensitivity >95% (Devlin et al 2007;Ezoddini Ardakani et al 2013;Kavitha et al 2013;Muramatsu et al 2013), while in other studies, this parameter did not reach 20% (Horner et al 2002;Marandi et al 2010;Mansour et al 2013). The same variability applied to the specificity levels (Appendix Table 4).…”
Section: Mandibular Cortical Widthmentioning
confidence: 89%
“…No significant difference was found between the OSTEODENT and FRAX indices when used as tests for therapeutic intervention. More recently Muramatsu et al (40) have developed an automated measurement system using a database of 100 DPRs from patients and volunteers, of whom 26 were diagnosed with osteoporosis. The group included both males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, for classification tasks, we observed the use of classifiers such as k-nearest neighbor (Filipczuk et al, 2013;Gedik and Atasoy, 2013;Gopinath and Shanthi, 2013;He et al, 2011;Muramatsu et al, 2013;Nava et al, 2014;Odeh et al, 2006;Osman et al, 2009;Raja et al, 2010;Verikas et al, 2006), artificial neural networks (Barhoumi et al, 2007;Geetha et al, 2008;Jasmine et al, 2009;López et al, 2008;Raja et al, 2007;Streba et al, 2012;Verma, 2009;Wu et al, 2006), Bayesian classifiers (Ampeliotis et al, 2007;Bhooshan et al, 2011;Garnavi et al, 2012;Gruszauskas et al, 2008Gruszauskas et al, , 2009Retter et al, 2013;Tolouee et al, 2011) techniques based on linear discriminant analysis (Lee et al, 2009;Muramatsu et al, 2013;Tanner et al, 2006) and logistic regression models (Shen et al, 2007;Tanner et al, 2006).…”
Section: Tasks For Computer-aided Diagnosis Systemsmentioning
confidence: 99%
“…(García-Orellana et al, 2008;Haindl et al, 2007;Muramatsu et al, 2013;Ramos et al, 2012;Song et al, 2010;Suganthi and Madheswaran, 2010;Verma, 2009;Wang et al, 2009;Zheng et al, 2008): maintained by the University of South Florida, this database serves as a resource for research in mammographic imaging analysis (Heath et al, 2001). The database contains 2,620 cases divided into 43 volumes, each composed of normal cases, cases containing suspicious structures proved benign or proven cases of cancer.…”
Section: Public Databases Of Medical Imagesmentioning
confidence: 99%